ANALISIS PERDAGANGA INTRA INDUSTRI SEKTOR MANUFAKTUR INDONESIA DENGAN ASEAN-4: Berdasarkan Hipotesis Industry Specific Dan Policy Based - Diah Wahyuningsih (MediaTrend, 2012)
The objective of this study is, first, to identify the dominant manufacture products in intra industry trade of ASEAN-5 and Indonesia with ASEAN-4 Countries (Malaysia,Thailand,Philipina and Singapore). Second, to analyze factors that influence the level of intra industry trade of intra ASEAN-5 and Indonesia with intra ASEAN-4, based on industry spesific and policy based hypothesis. Intra industry trade is measured by the use of Grubel and Lloyd indexes. Whenever the value of those two indexes are more than 40% then intra industry trade is happened, and if the value of those indexes is less than 40% then inter industry trade is occured.Methode of analuze in this study uses panel data with 19 industries as the cross-section data and the time period of the data is yearly data from 1998-2009. The study is focused on the analyzing on the relationship of intra industri trade of intra ASEAN-5 and between Indonesia with other ASEAN-4 countries after decreasing tariff policy into 0%-5% that is started in 2003.Result of this study shows that the development of indonesia intra industry trade in manufacture sector to intra ASEAN-5 market 1998-2009 periods, based on ISIC category, showed a fluctuative movement. this condition shows an inconsistency of the competitiveness of the treded manufacture commodities. Trede between Indonesia and Philipine is dominated by inter industry trade. This is because the traded products have different kind. the market power of the company/firm is able to influence the market and causing the increase of intra industry trade. hence, this will increase the production based on economies of scale on the trade between Indonesia, Malaysia, Thailand, Philipine and Singapore. Products that is trade in intra industry between Indonesia,Malaysia, Philipine. Thailand and Singapore are based on tecnological intensity. Lowering tariff policy into 0%-5% shows a positive and significant effect to intra industry trade with ASEAN-4 is dominated by vertical intra industry trade. This mean that trade is based on prodicts with the same characteristic but are difference in quality.